Working with the STYLE SQUAD: A Spanish perspective - López-Rodríguez, Fermín (Policy Press, 2018)
This short contribution is part of the STYLE handbook (http://style-handbook.eu/) and describes from a personal perspective the problem of youth unemployment in Spain. It is also commented very briefly some directions of improvement and the experience of the author with the research team of STYLE. STYLE is a research project that aims to examine the obstacles and opportunities affecting youth employment in Europe. The project includes 25 research partners, an international advisory network and local advisory boards of employers, unions, policy makers and NGOS from over 20 European countries.
Dado que proviene de una obra gestionada con una gran cantidad de autores, a partir de un proyecto europeo, y conseguir ahora los permisos de reproducción conllevaría mucho tiempo y gestiones, se ha optado por colgar la versión preprint del capítulo que se envió a la editora principal de la obra y cuyos derechos pertenece única y exclusivamente al autor. También se han añadido las páginas del capítulo en la cita, que está en inglés. Espero que con estos cambios pueda colgarse. Cualquier cuestión adicional, por favor, no duden en contactarme.
Keywords: Jóvenes - Trabajo; Youth unemployment; Spain; NEET; STYLE project